Protective effects of brain and muscle ARNT-like gene 1 on oxidized low-density lipoprotein-induced human brain microvascular endothelial cell injury by alleviating ferroptosis - Yu, Shui; Zeng, Yijun; Ruan, Chenbin; Bai, Lei; Liang, Zhang (Human & experimental toxicology, 2023)
Ferroptosis plays an important role in atherosclerotic cerebrovascular diseases. The brain and muscle ARNT-like gene 1 (BMAL1) is an important mediator in the progression of cerebrovascular diseases. However, whether BMAL1 regulates ferroptosis in atherosclerotic cerebrovascular diseases remains obscure. Here, human brain microvascular endothelial cells (HBMECs) were exposed to oxidized low-density lipoprotein (ox-LDL) to imitate cerebrovascular atherosclerosis. It was found that ox-LDL treatment induced ferroptosis events and reduced BMAL1 expression in HBMECs, which could be reversed by ferroptosis inhibitor ferrostatin-1. Furthermore, BMAL1 overexpression markedly mitigated ox-LDL-induced ferroptosis events and cell damage. Moreover, BMAL1 overexpression significantly promoted nuclear factor erythroid 2-related factor 2 (Nrf2) expression in HBMECs under ox-LDL conditions. And, Nrf2 silencing attenuated the protective effects of BMAL1 on ox-LDL-stimulated HBMEC damage and ferroptosis. Altogether, our findings delineate the cerebrovascular protective role of BMAL1/Nrf2 by antagonizing ferroptosis in response to ox-LDL stimulation and provide novel perspectives for therapeutic strategies for atherosclerotic cerebrovascular diseases.